Answer:
![\huge\boxed{x=-4}](https://tex.z-dn.net/?f=%5Chuge%5Cboxed%7Bx%3D-4%7D)
Step-by-step explanation:
![3(x+9)-4x=11x-13x+23\\\\(3)(x)+(3)(9)-4x=(11x-13x)+23\\\\3x+27-4x=-2x+23\\\\(3x-4x)+27=-2x+23\\\\-x+27=-2x+23\qquad|\text{subtrsact 27 from both sides}\\\\-x=-2x-4\qquad|\text{add}\ 2x\ \text{to both sides}\\\\x=-4](https://tex.z-dn.net/?f=3%28x%2B9%29-4x%3D11x-13x%2B23%5C%5C%5C%5C%283%29%28x%29%2B%283%29%289%29-4x%3D%2811x-13x%29%2B23%5C%5C%5C%5C3x%2B27-4x%3D-2x%2B23%5C%5C%5C%5C%283x-4x%29%2B27%3D-2x%2B23%5C%5C%5C%5C-x%2B27%3D-2x%2B23%5Cqquad%7C%5Ctext%7Bsubtrsact%2027%20from%20both%20sides%7D%5C%5C%5C%5C-x%3D-2x-4%5Cqquad%7C%5Ctext%7Badd%7D%5C%202x%5C%20%5Ctext%7Bto%20both%20sides%7D%5C%5C%5C%5Cx%3D-4)
Answer:
it's (6,0) I can't explain though
<h3>
Answer: 62.5%</h3>
Explanation:
There are 50+30 = 80 grams of sugar and water mixed together.
The percentage of sugar is 50/80 = 5/8 = 0.625 = 62.5%
<em>The </em><em>value</em><em> </em><em>of</em><em> </em><em>u</em><em> </em><em>is</em><em> </em><em>-</em><em>3</em><em>4</em><em>3</em>
<em>pl</em><em>ease</em><em> see</em><em> the</em><em> attached</em><em> picture</em><em> for</em><em> full</em><em> solution</em>
<em>Hope</em><em> </em><em>it</em><em> helps</em>
<em>Good</em><em> </em><em>luck</em><em> on</em><em> your</em><em> assignment</em>
Answer:
(-6,5)
Step-by-step explanation:
we have
y=f(x) ----> the parent function
y=1/2f(x) ---> the new y-value will be 1/2 times the original value
The rule of the transformation of f(x) to 1/2f(x) is
(x,y) -----> (x,y/2)
substitute the given value
(-6,10) ------> (-6,10/2)
(-6,10) ------> (-6,5)